Mucormycosis in COVID Pandemic and the Challenge for Anesthesiology and Critical Care: A Case Report - Naushad, Omar; Bashir, Muzamil; Faiz, Dawood; Deep, Palak; Rathee, Sonal; Sharma, Aditya; Kumar, Sumit (International Journal of Innovative Research in Medical Science, 2022)
Mucormycosis is a rapidly progressing fungal infection caused by filamentous fungi in the Mucoraceae family and is frequently seen in diabetic and immune-compromised patients. Mucormycosis is categorized as rhino-cerebral, pulmonary, cutaneous, and gastrointestinal or disseminated, depending on organ involvement; the most common form is rhino-cerebral (39%). This form may be divided into subtypes based on which tissues are affected: rhino-nasal, rhino-orbital or rhino-orbito-cerebral. Rhino-orbital infection begins when fungal spores are inhaled and invade the nasal mucosa, and sinusitis develops as the fungus spreads to the Para-nasal sinuses. Orbital involvement occurs when the infection invades the orbital wall from the Para-nasal sinuses. Symptoms may include pain, chemosis, vision loss, Ophthalmoplegia and proptosis. Ophthalmoplegia arises from infection of the muscles and orbital space or when the third, fourth and sixth cranial nerves are affected. Peripheral seventh cranial nerve paresis or paralysis and hypoesthesia of the face are often observed. We came across a 51-year-old male with multiple co morbidities suffering from rhino-orbito-cerebral mucormycosis. We present his pre, peri, and post operative management by anesthesiology and critical care department of Subharti medical college Meerut Uttar Pradesh. India.